2020
DOI: 10.1037/rep0000309
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of National Institutes of Health Toolbox Cognition Battery in pediatric brain injury rehabilitation settings.

Abstract: Objective: Cognitive impairments are a devastating consequence of acquired brain injury (ABI) in children. Current pediatric tools for assessing cognitive impairments are generally time intensive and applicable only to a restricted age span. The National Institutes of Health Toolbox–Cognition Battery (NIHTB-CB) is a standardized, tablet-based cognitive assessment that has been normed across the life span in the general population and validated in adults with brain injuries. However, its clinical utility and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Although the NIHTB-CB has been found to be a useful battery when considering Alzheimer's disease, the tests of memory may be too difficult and insufficiently sensitive for those at the lower end of memory function (Hackett et al, 2018;Ma et al, 2021). It has also been noted that children and adolescents with a high degree agitation (e.g., inhibition, emotional lability, and aggression) may not be able to complete the NIHTB-CB, as noted in a study with pediatric patients with acquired brain injuries (Watson et al, 2020). Such findings across clinical populations point to limitations of the NIHTB-CB that may also be applicable to patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NIHTB-CB has been found to be a useful battery when considering Alzheimer's disease, the tests of memory may be too difficult and insufficiently sensitive for those at the lower end of memory function (Hackett et al, 2018;Ma et al, 2021). It has also been noted that children and adolescents with a high degree agitation (e.g., inhibition, emotional lability, and aggression) may not be able to complete the NIHTB-CB, as noted in a study with pediatric patients with acquired brain injuries (Watson et al, 2020). Such findings across clinical populations point to limitations of the NIHTB-CB that may also be applicable to patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although we sought to identify records using the NIH Toolbox in clinical research, we identified 6 records reporting applications of NIH Toolbox measures in clinical settings (e.g., inpatient and outpatient medical clinics) for clinical purposes (e.g., to inform clinical practice and/or as part of routine care). These records demonstrated that the NIH Toolbox is feasible for use at rehabilitation settings with a pediatric brain injury population, [11][12][13] is minimally disruptive to the clinical operations of a multidisciplinary outpatient gastroenterology clinic, 16 is valid for use among older adults at different stages of cognitive health at a memory clinic, 15 and can serve as a rapid screening tool in the outpatient setting to identify patients at a high risk for severe encephalopathy. 14 These findings underscore the great potential of the NIH Toolbox for use in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The other category (n = 40, 14.2%) contained a variety of clinical diagnoses, While most records reported applications of the NIH Toolbox in research with clinical samples, 6 reported implementation in clinical settings. [11][12][13][14][15][16] Specifically, applications of NIH Toolbox Cognition Battery measures were reported among pediatric patients with brain tumors in both perioperative and follow-up inpatient and day treatment rehabilitation settings, [11][12][13] patients living with liver cirrhosis in an outpatient transplant clinic, 14 patients with dementia at a memory clinic, 15 and patients with celiac disease at a multidisciplinary outpatient gastroenterology clinic. 16 Study Design An observational study design was used in 39.9% (n = 112) of included records, compared with an experimental study design in 60.1% (n = 169).…”
Section: Clinical Diagnoses Representedmentioning
confidence: 99%
See 2 more Smart Citations